2019
DOI: 10.1111/are.14349
|View full text |Cite
|
Sign up to set email alerts
|

Mapping quantitative trait loci for infectious salmon anaemia resistance in a North American strain of Atlantic salmon

Abstract: Infectious salmon anaemia (ISA) is a highly virulent viral disease of Atlantic salmon that causes massive economic losses to infected aquaculture operations. Our goal was to detect and map quantitative trait loci (QTL) that confer resistance to ISA in an admixed commercial strain of Atlantic salmon that was largely founded from the Saint John River (SJR) in North America. Full‐sibling families were challenged with a virulent strain of ISA virus. Mortality was tracked during two annual trials with individual fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 84 publications
0
3
1
Order By: Relevance
“…Yet, four genomic regions explaining > 2.5% of the genetic variation in resistance to ISAV were detected. Two previous studies found resistance QTL for ISAV on chromosomes Ssa03, Ssa04, Ssa15 and Ssa25 [28,29], however, in our study, no signal of resistance was detected in these chromosomes; this is not surprising considering the different origins of the populations and the polygenic nature of resistance to ISAV (and the different nature of the challenge, through intraperitoneal injection, in [29]).…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Yet, four genomic regions explaining > 2.5% of the genetic variation in resistance to ISAV were detected. Two previous studies found resistance QTL for ISAV on chromosomes Ssa03, Ssa04, Ssa15 and Ssa25 [28,29], however, in our study, no signal of resistance was detected in these chromosomes; this is not surprising considering the different origins of the populations and the polygenic nature of resistance to ISAV (and the different nature of the challenge, through intraperitoneal injection, in [29]).…”
Section: Discussioncontrasting
confidence: 75%
“…Several studies have shown that host resistance to ISAV has a significant additive genetic component in Atlantic salmon, with heritability estimates ranging from 0.13 to 0.40 [23][24][25][26][27]. Furthermore, studies using molecular markers to investigate the genetic architecture underlying this heritability have revealed putative QTL on chromosomes 3, 4, 15 and 21 [28,29], and a comparative genomic analysis highlighted potential underlying genes [30]. Several studies have also examined the host response to ISAV by profiling gene expression in tissues and cell lines [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous studies using co-habitation have used a higher proportion of ‘Trojan’ fish, which may result in a higher infection pressure and differences in host response [ 37 ]. Finally, the genetic correlation between resistance to ISAV in freshwater (this study, [ 28 ]) and seawater [ 29 ] should be addressed in future studies; the life stage of the fish can have an important impact on resistance to ISAV and could also explain some of the differences between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Infectious salmon anaemia 178,179 Pancreas disease 180,181 Piscine myocarditis virus [182][183][184] Amoebic gill disease [185][186][187] Sea lice 65,188,189 Infectious pancreatic necrosis 81,154,190,191 Piscirickettsia salmonis 192…”
Section: Atlantic Salmonmentioning
confidence: 99%